The city of Khemis Miliana in ancient times..in foreign historical writings and through archaeological remains - azzizi, Sara (The Algerian Historical Journal, 2026)
This study will not delve into the history of the city of Khemis Miliana in its various aspects, but rather present the foreign historical writings that were written about the city, especially what was written by those who came to the city and carried out archaeological studies around it and recorded it in their writings. Thus, they revealed the name by which the city was known in the Roman period, which is Manliana or Malliana, and therefore its history, with a difference in determining whether the Phoenician city Zucchabar, whether it refers to it or to its neighboring cities. The study will also show the archaeological remains that was found in the city and is still present in the city, and which dates back to the ancient times of its history.